Stability of Geometrically Recurrent Time-inhomogeneous Markov Chains - Vitaliy Golomoziy (Austrian Journal of Statistics)
This paper is devoted to establishing upper bounds for a difference of n-step transition probabilities for two time-inhomogeneous Markov chains with values in a locally compact space when their one-step transition probabilities are close. This stability result is applied to the functional autoregression in R^n.